Combating Corruption in Indonesia: Digital Evidence in Criminal Prosecution - Yati Vitria; Abdul Basid (INFOKUM, 2025)
This study investigates the role and effectiveness of digital evidence in the criminal prosecution of corruption cases in Indonesia. With the growing prevalence of technologically mediated corruption ranging from encrypted financial transactions to manipulated digital documentation traditional legal frameworks face substantial challenges in ensuring evidentiary reliability, procedural fairness, and institutional coordination. Employing a qualitative case study approach, this research draws on in-depth interviews and documentary analysis to examine the institutional, legal, and technical dimensions of digital evidence utilization within the Indonesian justice system. Findings reveal persistent barriers, including the absence of comprehensive legal standards for digital evidence authentication, limited forensic capacity among law enforcement personnel, and fragmented inter-agency cooperation. These structural limitations not only hinder prosecutorial effectiveness but also compromise the integrity of judicial outcomes. In response, the study proposes a multi-layered framework encompassing regulatory reform, capacity-building, and procedural standardization to facilitate the lawful, secure, and effective use of digital evidence. By integrating digital forensic tools into legal practice, Indonesia’s anti-corruption enforcement can enhance prosecutorial accuracy, judicial trust, and overall institutional resilience.